TAJRIBA GURUHIDAGI SIGIRLARNING PUSHTDORLIK KO‘RSATKICHLARI - Nomozova., O.; Pardayev., R.; Shaptakov, E. (INTERNATIONAL CONFERENCES, 2022)
Experimental study of the fertility of Qora-ola cows, their service period, live weigt, the period from weaning to weaning and the escape index in two groups.